2012
DOI: 10.1155/2012/984780
|View full text |Cite
|
Sign up to set email alerts
|

Caffeic Acid Phenylethyl Amide Protects against the Metabolic Consequences in Diabetes Mellitus Induced by Diet and Streptozocin

Abstract: Caffeic acid phenyl ester is distributed wildly in nature and has antidiabetic and cardiovascular protective effects. However, rapid decomposition by esterase leads to its low bioavailability in vivo. In this study, chronic metabolic and cardiovascular effects of oral caffeic acid phenylethyl amide, whose structure is similar to caffeic acid phenyl ester and resveratrol, were investigated in ICR mice. We found that caffeic acid phenylethyl amide protected against diet or streptozocin-induced metabolic changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 61 publications
(26 citation statements)
references
References 36 publications
(37 reference statements)
1
25
0
Order By: Relevance
“…In STZ-induced type 1 diabetic rats, CAPA lowered plasma glucose levels even though this diabetic rat model has low insulin secretion activity, suggesting that insulin-independent mechanisms may be involved. Our findings were concordant with those studies that reported plasma glucose lowering activity of CAPA in STZ-induced type 1 diabetic mice [35] and increased glucose transporter 4 protein expression along with insulin-induced glycogen synthesis in diet-induced type 2 diabetic mice [10]. The detailed mechanism responsible for the antidiabetic activity in type 1 diabetic rats remains to be investigated.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In STZ-induced type 1 diabetic rats, CAPA lowered plasma glucose levels even though this diabetic rat model has low insulin secretion activity, suggesting that insulin-independent mechanisms may be involved. Our findings were concordant with those studies that reported plasma glucose lowering activity of CAPA in STZ-induced type 1 diabetic mice [35] and increased glucose transporter 4 protein expression along with insulin-induced glycogen synthesis in diet-induced type 2 diabetic mice [10]. The detailed mechanism responsible for the antidiabetic activity in type 1 diabetic rats remains to be investigated.…”
Section: Discussionsupporting
confidence: 93%
“…Streptozotocin (STZ) is the most frequently used drug to induce diabetes and has been useful for the study of multiple aspects of the disease [9]. In the cardiovascular system, studies have shown decreased basal coronary arterial flow in STZ-induced diabetic mice [10], decreased aortic blood flow in STZ-induced diabetic rats [11], and decreased sensitivity to phenylephrine of vascular tissues in type 1 diabetic rats [12]. In addition, nitric oxide (NO) production is reduced in STZ-induced diabetes, and the decrease in NO may be related to the pathogenesis of diabetic endothelial damage [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1) was synthesized using the amide-binding coupling method as previously described (Chuang et al, 2014;Weng et al, 2012aWeng et al, , 2012b. …”
Section: Chemicalsmentioning
confidence: 99%
“…Caffeic acid phenethyl ester (CAPE) is also a polyphenolic compound with anti-oxidant, anti-inflammation and anti-fibrosis effects. However, rapid decomposition by esterases reduces its bioavailability in vivo (Chuang et al, 2014;Wang et al, 2007;Weng et al, 2012a). Caffeic acid phenylethyl amide (KS370G) is a synthetic caffeamide derivative and has been reported to exert hypoglycemic effects in diet and streptozocin-induced diabetic mice (Weng et al, 2012a) and cardiovascular protection in pressure-overloaded mouse hearts (Weng et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%